The Nexus of Service Quality, Student Satisfaction and Student Retention in Small Private Colleges in South Africa - Chukuakadibia Eresia-Eke; Nokulunga Ngcongo; Tumelo Ntsoane (MDPI AG, 2020)
Small private colleges provide an important service to society while operating in a dynamic and competitive environment. The inability to operate in a manner that delivers desirable levels of satisfaction to students can prove fatal, more so given the relatively small size of their student populations. So, for these colleges, student retention is a critical condiment of business success and so the pursuit of service quality becomes amplified. In acknowledgement of the subjective nature of service quality that makes service quality studies very context specific, this empirical study takes a quantitative research approach to investigate the extent of association, if any, between service quality dimensions, student satisfaction and student retention in the specific context of small private colleges in South Africa. Study findings indicate the existence of statistically-significant positive (though moderate) associations between dimensions of service quality and student satisfaction as well as between student satisfaction and student retention. Though results ought not to be generalized, the study's findings nonetheless, bode useful lessons for small private colleges, if the quest for improved business performance, based on student retention, is to be realized.